The musical as drama : a study of the principles and conventions behind musical shows from Kern to Sondheim - McMillin, Scott, 1934-2006 (Princeton University Press, 2006)
"Discussing composers and writers such as Rodgers and Hammerstein, Stephen Sondheim, Kander and Ebb, Leonard Bernstein, and Jerome Kern, The Musical as Drama describes the continuity of this distinctively American dramatic genre, from the shows of the 1920s and 1930s to the musicals of today."--Jacket